Pengaruh Pengembangan Karir dan Kompensasi terhadap Retensi Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada CV. Clean & Clear Indonesia Bogor - Aditia Muhammad; Samsuri Samsuri; Ismartaya Ismartaya (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the influence of career development and compensation on employee retention with job satisfaction as an intervening variable at CV. Clean & Clear Indonesia Bogor. This research employed a quantitative approach using saturated sampling with 100 respondents. Data were collected through questionnaires containing structured statements and analyzed using multiple linear regression and path analysis with SPSS version 27. The results indicate that career development has a negative effect on job satisfaction, while compensation shows no direct positive effect on job satisfaction. Furthermore, career development positively affects employee retention, whereas compensation has a negative effect on employee retention. Job satisfaction has no significant negative effect on employee retention and does not mediate the effect of career development on retention. However, job satisfaction is found to mediate the effect of compensation on employee retention. The findings highlight that optimizing career development programs and fair compensation systems are essential strategies for enhancing employee satisfaction and improving retention in service-oriented organizations.